Pegylated interferon-alpha plus taurine in treatment of rat liver fibrosis - Tasci, Ilker (World J Gastroenterol, 2007)
AIM: To investigate the antifibrotic effects of peginterferon-alpha 2b and taurine on oxidative stress markers and hepatocellular apoptosis. METHODS: Sixty rats with CCl4-induced liver fibrosis were divided into 4 groups (n = 15). Group 1 was left for spontaneous recovery (SR). Groups 2-4 received peginterferon-alpha 2b, taurine, and their combination, respectively, for four weeks. Histological fibrosis scores, histomorphometric analysis, tissue hydroxyproline, tissue MDA, GPx and SOD activities were determined. Activated stellate cells and hepatocellular apoptosis were also evaluated. RESULTS: The degree of fibrosis decreased in all treatment groups compared to spontaneous recovery group. Taurine alone and in combination with peginterferon-alpha 2b reduced oxidative stress markers, but peginterferon-alpha 2b alone did not. Apoptotic hepatocytes and activated stellate cells were higher in groups 2-4 than in group 1. Combined taurine and peginterferon-alpha 2b further reduced fibrosis and increased activated stellate cell apoptosis, but could not improve oxidative stress more than taurine alone. CONCLUSION: Peginterferon-alpha 2b exerts anti-fibrotic effects on rat liver fibrosis. It seems ineffective against oxidative stress in vivo. Peginterferon-alpha 2b in combination with taurine seems to be an antifibrotic strategy.